Kurikukulum Merdeka: Problematik Guru dalam Implementasi Teknologi Informasi pada Proses Pembelajaran - Aulia, Aan Fitri; Asbari, Masduki; Wulandari, Siti Ayu (Journal of Information Systems and Management (JISMA), 2024)
The use of technology in education has become a major focus to improve the quality of learning in Indonesia. However, many teachers face a number of problematic issues in adopting and utilizing Technology in the learning system. The purpose of this study is to identify and analyze the challenges faced by teachers in Implementation Technology Information in the learning process. This study report uses a descriptive qualitative method by doing simak catat because the data system is obtained by listening to oral narratives from the youtube channel news one entitled "Encourage changes in the world of education" presented by gembul teacher. The results of this study explain that other problematic issues identified include data security and privacy issues, lack of resources for Technology device maintenance, and the digital divide among students. Improvement efforts include increased teacher training in Technology utilization, improved Technology infrastructure in schools, and policies that support the integration Technology Information in the curriculum. By addressing these issues, teachers in Indonesia can more effectively utilize information technology to improve the quality of education and provide better learning experiences for students.